IDENTIFIKASI GALUR Ralstonia solanacearum DENGAN HIBRIDASI SLOT BLOT DNA - Y suryadi (BERITA BIOLOGI, 2003)
R. solanacearum (RS), the casual agent of bacterial wilt is one of the most destructive pathogen in the tropical and sub tropical areas that affected various economic crops. Since the pathogen is very diverse, it is necessary to identify the variation of RS isolates. The Polymerase Chain Reaction (PCR) was used in this study to amplify 16S rRNA gane. Two DNA primer pairs namely pr#a and pr#b were used as probe to identify thirtyfour strains of Rs respresenting different biovars isolated from various host. The DNA probes were labelled using digoxygenin and deteced by DNA slot blot hybridization. Resutl showed that the DNA probes colud hybridzed specifically with target DNA, hence distinguish variation of Rs isolates. This assay will be of futher used in the strain identification of Rs from wide range of host from various geographic distribution.